Nikah Bacindua in The Perspective of Mashlahah Mursalah in South Batipuh District, Tanah Datar Regency, West Sumatra - Hamdani, Hamdani; Yanto, Fendri; Afiza, Fadiah Nur (Alhurriyah, 2024)
The principal goal of marriage is to build a sakinah family, as described in the Al-Qur'an Surah Ar-Rum (30:21). However, this noble goal cannot be realized as it should be since the increase in divorce cases. Paradoxically, there is remorse among divorced couples due to the demand for children and other psychosocial factors. This study looks at the practice of tahlil marriage, or what is known as bacindua. This study is field research. The perpetrators of the tahlil marriage, niniak mamak, religious scholars, and community leaders were the primary informants of the research. The research findings showed that tahlil marriage occurs when the husband has already divorced his wife with three kinds of pronouncements of divorce, either three at once or three sequentially. Some people understood that the third talaq, which is declared simultaneously, means triple talaq. This condition triggers the practice of tahlil marriage, in which the wife is told to marry the man her husband is looking for and marry at any time with the help of a person who is considered a religious figure (Angku). It was also found that bacindua has benefits (mashlahah), which are to protect the offspring produced from marriage to the first husband and for the benefit of the children's future. Nevertheless, the practice of tahlil marriage is contrary to the text of the Qur’anic verses and the hadith. Thus, in terms of the benefits, the practice of this type of marriage is categorised as maslahah mulghah.